The influence of 110-Ritcher and SO4 rootstocks on the performance of scions of Vitis vinifera L. cv. Albariño clones - Boso, S.; Santiago, J.L.; Martínez, M.C. (Spanish Journal of Agricultural Research, 2008)
The use of rootstocks is widespread in modern viticulture; non-grafted Vitis vinifera vines are now grown in only a handful of places with very specific conditions. Since the need to graft vine-scions onto American rootstocks, a lot of work has been performed in which different aspects of the relationship between the vine and the rootstock have been studied. Despite this there are still many open questions, which remained unanswered. The present paper reports a study performed on five "Albariño" clones (MBG-1, MBG-2, MBG-7, MBG-9 and MBG-10), in which the influence of rootstock type (110- R and SO4) on a number of agronomic variables was examined. The results show that these rootstocks have no influence on many of the variables which were studied (phenology, cluster size and weight, fertility, yield, and berry size and weight), although they do influence variables such as the probable alcohol content, the quantity of free-run juice, must total acidity and weight of pruned wood. Therefore it is possible to conclude, that rootstocks influence agronomic parameters.